The Question of Linguistic Nationalism in Medieval Bohemia - Toman, Jindřich (Cahiers du Centre de Linguistique et des Sciences du Langage, 2022)
The present paper is a brief and in all respects preliminary presentation which documents the link between language and group identity in medieval Bohemia and discusses the question whether the link provides any evidence for early Czech nationalism. The point of departure is the so-called Dalimil Chronicle, a text dating from 1314. The chronicle, one of the oldest long texts in Czech, is fairly well known in Czech studies, where is has often been recognized, among other things, for its rather explicit anti-German sentiment.